Assistance In Developing a Geragogy-Based Religious Curriculum to Enhance the Spiritual and Physical Well-Being of The Elderly, Bogor - Ali, Agus; Hidayaturahman, Muhamad (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2025)
The objective of this community service program is to provide assistance in the development of a geragogy-based religious curriculum aimed at improving the spiritual and physical well-being of the elderly. By utilizing the potential of existing human resources at the elderly Islamic boarding school (pesantren lansia) and through collaboration with various stakeholders, it is expected that following the implementation of the Student Creativity Program (Program Kreativitas Mahasiswa/PKM), the teachers at Al-Hikmah Elderly Islamic Boarding School in Cibungbulang, Bogor, will be able to quickly understand and apply the geragogy-based religious curriculum. This curriculum is specifically designed to enhance both the spiritual and physical quality of life of elderly learners. The implementation of this community service program consists of several key stages: identification of educational quality, quality enhancement, network development, mentoring, and monitoring. The results of the program indicate that Al-Hikmah Elderly Islamic Boarding School in Cibungbulang, Bogor, has implemented a number of effective strategies, including: a) the development of a geragogy-based religious curriculum that involves the design of teaching methods and overall learning organization; b) the provision of core textbooks; c) the procurement of educational equipment; d) training for the teaching staff and lecturers; and e) the availability of high-quality literature that promotes both mental and physical well-being. In conclusion, Al-Hikmah Elderly Islamic Boarding School in Cibungbulang, Bogor, has actively implemented various geragogy-based religious curriculum strategies to support the spiritual and physical welfare of its elderly community.